Popularization of science in the current social and cultural situation - Elena Alexandrovna Panina (Вестник Майкопского государственного технологического университета)
The aim of the research is the process of popularization of scientific knowledge in the modern social and cultural space. Currently, the Russian authorities are making efforts to systematize work to popularize scientific knowledge, and are actively developing forms and methods of educational activity. In this regard, the issues of interaction between the science and the state acquire special significance and relevance. The author has examined the problems of the emergence of modern interactive methods of popularization, sometimes lying in the “entertainment plane”, which coexist with traditional forms and methods of educational work. Special attention is paid to the preparation of popular science content for the general public. It has been revealed that the participation of specialists in mass communication is necessary for the effectiveness of the process of presenting the results of scientific research of a mass audience. According to the author, this is due to an increase in the number of professionals who receive indepth knowledge of natural and STEM disciplines and are ready for effective work in the field of scientific communications. The forms and means of presenting scientific research of the mass audience selected by the participants of scientific communication are also the subject of the analysis in the article. The research methods used are theoretical analysis, synthesis and generalization.